Aberrant interhemispheric functional connectivity and cerebral blood flow in vascular dementia (VD) and non‐amyloid mild cognitive impairment (NamyMCI). (1st February 2022) - Cheung, Eva YW; Shea, Yat Fung; Chiu, Patrick Ka‐Chun; Kwan, Joseph SK; Mak, Henry
Abstract: Background: Previous studies have demonstrated that functional connectivity and relative cerebral blood flow were altered in patients suffered from Alzheimer's disease (AD) and Mild cognitive impairment (MCI). However, the application on vascular dementia (VD) and non‐amyloid mild cognitive impairment (VMCI) are still unclear. Method: 65 participants (18 healthy controls HC, 16 AD, 18 NamyMCI, 13 vascular dementia (VD)) were recruited, from the university hospital memory clinic, to undergo MRI scanning. All participants underwent structural MRI, resting state functional MRI (rs‐fMRI) scanning and pseudo continuous arterial spin labelling (pCASL) with post‐labelling delay time at 2000ms in the same session. Voxel Mirrored Homotopic Connectivity (VMHC) was calculated based on the method used by Kelly et al., 2011 [1] and Zuo et al., 2010 [2]. The analysis of pCASL images performed using ASL‐MRICloud by Li et al., 2017 [3]. White matter hypointensities on T1‐weighted 3D anatomical images of each individual was calculated using FreeSurfer image analysis suite 6.0. Group differences in VMHC, absolute CBF and relative CBF were determined by performing whole brain voxel‐wise ANCOVA analysis on subject‐specific VMHC maps, absolute CBF maps and relative CBF maps respectively, with age, gender and GM volume as covariates. To identify the significant associations between IFC and CBF, a voxel‐wise correlation analysis was conducted using the DPABI v 4.0. Result: Both IFC and CBF were reduced in AD group. However there is no significant relationship found in correlation analysis. For NamyMCI group, negative correlation were found in precuneus, cuneus, calcarine, superior frontal gyrus and insula. For VD, positive correlation was found in superior frontal gyrus, inferior frontal orbital gyrus, rolandic operculum and superior temporal gyrus. Also, the T1 white matter hypointensity volume was significantly larger than that of the other groups (p<0.001). Conclusion: IFC reduction in AD was independent to CBF reduction, probably related amyloid deposition. For NamyMCI, negative correlation suggested that CBF increases to compensate the attenuated IFC to maintain daily functions. For VD, CBF reduction relates positively with IFC, suggested the CBF reduction is one of the factors contributed to IFC reduction in VD.